Health and Wellbeing Consultation System (HBCS): Promoting Flexibility in Managing Disease and Medical Appointment - Sapawi, Nur Anis Nabilah Mohd; Saad, Sharhida Zawani (Multidisciplinary Applied Research and Innovation, 2023)
With the growth of technology, people nowadays depend on systems that help to assist, organize and solve their daily routines and problems. In today’s hectic and challenging life, we need a reliable platform to consult about healthcare more efficiently. The Health and Wellbeing Consultation System (HBCS) is developed in order to replace the existing manual system due to limitations of manual systems and procedures. The traditional method of gaining consultation, awareness, relevant information, appointments and treatments can sometimes be ineffective due to time and space constraints compared to utilizing consultations or booking systems. The HBCS can be a quick platform to obtain quick, relevant medical information and awareness. For example, users may select diseases and obtain crucial information such as the names, causes, symptoms, related information and options of potential treatment. Specific information can be hard to obtain yet very essential in our daily life. The main objective of HBCS is to provide a quick platform in consulting, obtaining information, awareness, as well as seeking for urgent advice, treatments and medications. Rapid Application Development (RAD) is used to develop the system. This methodology consists of four stages, namely requirement planning, user design, rapid construction and cutover phases. First, the functional requirements were gathered through interviews and content analysis. Then, the HBCS was developed based on the gathered requirements. A field study was carried out to evaluate the usability of the prototype. The results of the evaluation suggest that the HBCS is useful and easy to use. The study contributes towards an understanding of the system requirements and user interfaces of a Web-based system for booking and consultation purposes in supporting health and wellbeing demands. It can be a reference model for similar Web applications or enhance the capabilities in treating and managing patients better.